Explanation the Functional principals of Spatial Governance in trans structure framework methodology - Ehsan Lashgari Tafreshi; َabbas Ahmadi (تحقیقات کاربردی علوم جغرافیایی)
The emergence of decentralization approach and transfer some political authority to non-state actors has provided new actions for the management of geographical space under the name of spatial governance. The roots of the emergence of the concept of spatial governance return to the economic-political changing in the 1980s. The emergence of a decentralization approach and the transfer powers from government to nongovernmental institutions has provided a new concept in the name of "spatial governance". Therefore, governance is beyond the government and includes the private sector and civil society with the approach of market economy and participatory democracy. So, in this paper major question is “who spatial governance functioned in the post- positivism methodology?” In this regard, in the first step has been made to define the concept of governance and its dimensions and sub-sets in relation to geographical space. Then, by matching the spatial governance conceptual relationship with post-positivism approach, a new perspective on the causes of the greater impact of this school is presented in understanding this concept. According to the governance framework, the management and production of space is not only an objective or objective action, but also it is a constructive, unfinished, contingent, and conditional, conditional and social condition. therefore, the space policy was created in a cultural-historical territory must be consistent with the cultural and historical values of a particular of human beings group and the conditions for the development and optimization of space by these policies should fit into the pattern of their social life. in governance approach, some of the concepts such as truth, rationality, justice, goodness, and especially development, are not independent from its the social processes that shape it. On this basis, spatial governance cannot have universal dimensions.  Because social action is faced with a process that can create a single position at any given time, pro-active methodology cannot predict and predict it.